2002
DOI: 10.1089/10872910252806117
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Virologic Failure among HIV-Positive Injecting Drug Users Treated with Combination Antiretroviral Therapy Including Two Nucleoside Reverse Transcriptase Inhibitors and Nevirapine

Abstract: Treatment strategies in human immunodeficiency virus (HIV)-positive active injecting drug users (IDUs) must take into account their lifestyles, that often result in low adherence to therapy. The nonnucleoside reverse transcriptase inhibitors (NNRTI) offer simpler treatment regimens, but the appearance of drug resistance during treatment failure may cause high levels of cross-resistance to all NNRTIs. We adopted a combination therapy of two NRTIs and nevirapine (NVP) for treatment of IDU patients to evaluate it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Our data showed that the probability of EFV interruption (nearly 30% after 48 months) was similar to that observed in Italy at the beginning of the EFV availability [18]. However, we also observed that the improved EFV formulation had a positive effect on the risk of interruption.…”
Section: Discussionsupporting
confidence: 86%
“…Our data showed that the probability of EFV interruption (nearly 30% after 48 months) was similar to that observed in Italy at the beginning of the EFV availability [18]. However, we also observed that the improved EFV formulation had a positive effect on the risk of interruption.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, access to substitution therapy was strongly associated with optimal virologic response in studies of community-recruited drug users in France [66] and Canada [55]. Five studies [29, 44, 47, 50, 76] observed virologic trajectories following the initiation of HAART. Notably, in three [44, 47, 50] of four studies assessing them [44, 47, 50, 76], drug use patterns were not associated with lower relative hazards of suppression.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies on early HAART responses among injection drug users (IDUs) tend to suggest that while IDUs as a group may be as likely to suppress HIV-1 RNA (Mocroft et al, 1999;Roca et al, 1999), active users tend to have poorer responses while former users can achieve similar responses to non-IDUs (Arnsten et al, 2002;Lucas et al, 2001;Lucas et al, 2006;Palepu et al, 2003;Wood et al, 2003;Zaccarelli et al, 2002). In some cases faster disease progression has also been observed among IDUs (Lucas et al, 2006), although few studies have linked to clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%